Neural Correlates of Reactive Aggression in Adult Attention-Deficit/Hyperactivity Disorder - Jakobi, Babette; Arias-Vasquez, Alejandro; Hermans, Erno; Vlaming, Priscilla; Buitelaar, Jan; Franke, Barbara; Hoogman, Martine; van Rooij, Daan (Frontiers in Psychiatry, 2022)
Despite not being part of the core diagnostic criteria for ADHD, emotion dysregulation is a highly prevalent and clinically important component of (adult) ADHD. Emotion dysregulation has a significant impact on the functional outcome in ADHD, for example through reactive aggression. However, little is known about the mechanisms underlying such emotion dysregulation symptoms. In this study, we aimed to identify the neural correlates of reactive aggression in adults with persistent ADHD during implicit emotion regulation processes. We analyzed associations of magnetic resonance imaging-based whole-brain activity during a dynamic facial expression task with levels of reactive aggression in 78 adults with and 78 adults without ADHD, and also investigated relationships of reactive aggression with symptoms and impairments. While participants with ADHD had higher reactive aggression scores than controls, the neural activation patterns of both groups to processing of emotional faces were similar. However, investigating the brain activities associated with reactive aggression in individuals with and without ADHD showed an interaction of diagnosis and reactive aggression scores. We found high levels of activity in the right Insula, the hippocampus, and middle and superior frontal areas to be particularly associated with high reactive aggression scores within the ADHD group. Furthermore, the limbic activity was associated with more hyperactivity/impulsivity symptoms. These results suggest a partly differential mechanism associated with reactive aggression in ADHD as compared to controls. Emotional hyper-reactivity in the limbic system and insula as well as more effortful top-down regulation from medial frontal areas might contribute to emotionally dysregulated behavior as measured by reactive aggression.